2022
DOI: 10.21203/rs.3.rs-1277436/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceived Ideal Number of Children Among Adolescents in Sub-Saharan Africa: Does Exposure to Family Planning Messages Matter?

Abstract: BackgroundEven though evidence shows that fertility transition has begun almost everywhere in sub–Saharan Africa, the decline has been slower than in other parts of the world. Researchshows that there is a positive relationship between fertility levels and desired family size. Therefore, many countries in the region are implementing family planning education campaigns targeting at influencing reproductive behaviour of women. Thus,this studyaimed at examiningthe extent to which exposure to family planning commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…It is plausible that women who live in countries with high social globalisation index would be more likely to use maternal healthcare compared to their counterparts who do not. Several studies have demonstrated the crucial role played by exposure to the media as well as civil and socio-economic rights in maternal and reproductive health matters [33][34][35] . Promotion of civil, media, technology, and communication freedoms shape culture, enhance citizen awareness about their rights, and influence national politics which may in turn lead to better provision, access, and utilisation of health services.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that women who live in countries with high social globalisation index would be more likely to use maternal healthcare compared to their counterparts who do not. Several studies have demonstrated the crucial role played by exposure to the media as well as civil and socio-economic rights in maternal and reproductive health matters [33][34][35] . Promotion of civil, media, technology, and communication freedoms shape culture, enhance citizen awareness about their rights, and influence national politics which may in turn lead to better provision, access, and utilisation of health services.…”
Section: Discussionmentioning
confidence: 99%